2019
DOI: 10.3389/fnbeh.2019.00053
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Changes in Cardiorespiratory Fitness and Symptoms of Anxiety and Depression With Brain Volumes: The HUNT Study

Abstract: Objective: We investigated the independent and joint associations of changes in estimated cardiorespiratory fitness (eCRF) and symptoms of anxiety and depression with brain volumes in individuals from the general population. Method: 751 participants (52% women, aged 50–67 years) from the Nord-Trøndelag Health Study (HUNT) MRI cohort were included. eCRF obtained from a non-exercise algorithm and symptoms of anxiety and depression were assessed twice; at HUNT2 (1995–97) and HUN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…A plausible explanation for this finding is that individuals who display higher levels of physical fitness tend to have more positive perceptions of anxiety symptoms and thus feel less anxious (25). This supposition is supported by several studies that have shown that improvements in physical fitness are associated with reductions in levels of anxiety ( 43 45 ). However, Rodriguez-Ayllon et al ( 19 ) found no relationship between physical fitness components and anxiety indicators.…”
Section: Discussionmentioning
confidence: 72%
“…A plausible explanation for this finding is that individuals who display higher levels of physical fitness tend to have more positive perceptions of anxiety symptoms and thus feel less anxious (25). This supposition is supported by several studies that have shown that improvements in physical fitness are associated with reductions in levels of anxiety ( 43 45 ). However, Rodriguez-Ayllon et al ( 19 ) found no relationship between physical fitness components and anxiety indicators.…”
Section: Discussionmentioning
confidence: 72%
“…5 Observational studies using brain MRI measures as proxies for brain health and AD risk report positive associations between CRF and brain structures involved in the pathophysiology of AD such as the hippocampus and cortex. [6][7][8][9][10] However, there are contradictory findings regarding the presence of such positive effects. Randomized controlled trials (RCT) and other exercise intervention studies in community dwelling and hospital cohorts of younger and older adults report predominantly positive effects of moderate intensity exercise on the brain, with greater hippocampus and cortex volume in the exercise group compared to controls.…”
Section: Introductionmentioning
confidence: 99%
“…The HADS contains 14 items, of which 7 assess anxiety symptoms (HADS-A) and 7 assess depressive symptoms (HADS-D). For respondents who had completed 6 items on HADS-A time 1 ( n = 8), HADS-A time 2 ( n = 12), HADS-D time 1 ( n = 10) and HADS-D time 2 ( n = 4), the sum was multiplied by 7/6 to calculate the total score, an approach that has been used elsewhere [ 32 ]. A cut-off of 8 was used to determine symptom severity indicative of a clinical symptom level.…”
Section: Methodsmentioning
confidence: 99%